Robotic pedicle screw placement for minimal invasive thoracolumbar spine surgery: a technical note - Gatam, Luthfi; Phedy, Phedy; Husin, Syafruddin; Mahadhipta, Harmantya; Rizki Gatam, Asrafi; Mitchel, Mitchel; Gani, Karina Sylvana; Kholinne, Erica (Frontiers in Surgery, 2025)
BackgroundPedicle screw placement in spine surgery is a complex and delicate procedure that requires precise and accurate placement of pedicle screws. This technical note describes the steps involved in performing robotic assistance pedicle screw insertion in thoracolumbar spine surgery using the ExcelsiusGPS platform.MethodsThis paper outlines the surgical techniques and intraoperative workflow for pedicle screw placement using the ExcelsiusGPS system. It also covers the surgical process, including patient positioning, dynamic reference placement, intraoperative cone-beam tomography, screw planning, exposure, and insertion techniques for spinal stabilization.DiscussionA meta-analysis highlighted the significant advantages of robotic spine surgery over traditional freehand techniques, including a notably lower complication rate (4.83% vs. 14.97%) and up to a tenfold reduction in surgeon radiation exposure compared to fluoroscopy. Additionally, robotic systems enhance pedicle screw placement accuracy, achieving a 91.7% success rate. This higher accuracy is attributed to real-time screw planning, trajectory guidance, and precise adjustments in robotic-assisted surgery. These advantages establish robotic assistance as a crucial innovation for enhancing surgical precision and patient safety, although it requires careful handling of technical challenges like alignment changes in highly flexible bones and ensuring accurate instrument trajectory during screw placement.ConclusionRobotic-assisted spine surgery improves pedicle screw accuracy with real-time planning and trajectory adjustments, reducing complications and radiation exposure. However, higher costs and increased screw use warrant careful evaluation of its cost-effectiveness and impact on healthcare resources.